UTILIZATION OF CONVERSION TECHNIQUE IN WRITING OF WORKS - Yulina Mingvianita (Jurusan Sastra Indonesia, 2019)
Literature as a work of art that has meant a sign or symbol that is defined by language. The language used strawn as the author or authors of literary works become baselines conceptual gave understanding to the reader. Language as the basis of communication between writers and readers of literary works. language in literature is poured through the text to give meaning to literary readers in producing words, phrases, sentences, and symbols in literary works. the meaning of the language in the text of literary writing using communicative language, lively, flexible, loose, and original in its utilization. This can be done with conversion techniques to change the elements of a modified sentence without altering the meaning of the previous form.